POTENSI DAN KONSERVASI JENIS-JENIS HOYA DATARAN TINGGI PULAU JAWA - Sri Rahayu (The East Java Biological Society, 2012)
Hoyas (Hoya Sp.: Asclepiadoideae - Apocynaceae) has been utilized as ornamental plant especially in Europe and the USA. The original distribute from the South of India to Samoa, and from South of Japan to the North –East of Australia. Altitudinal distribution from the sea level to about 2000m. According to the thermoecological concept by Van Steenish, altitudinal distribution of plant correlated with the latitudinal distribution regarding with the environmental temperature. The lowland plant prefer to higher temperature and distribute in arround the eqator, while high altitude plant able to adapt in temperate zones. The inventory of high altitude Hoya specieshas been conduct in Java by fl ora exploration during 1996–2011. The species can be utilized as ornamental plant for export trade to Europe and USA. There were eight species of Hoya in high altitude of Java, six of them have wide altitude range distribution, while the two species i.e. H. kuhlii (Blume) Koorders and H. purpureofusca Hook. evolve restricted distribution only at the high altitude of Java/Bali above 1000m. H. wrayi King & Gamble only found once at 1200 m in East Java, but this species has been found in lower altitude in Sumatra. Species which have wide range altitudinal distribution i.e. H. campanulata Blume, H. lacunosa, H. latifolia G. Don, H. lasiantha Korth., H. multifl ora Blume and H. wrayi Kimg & Gamble, able to adapt in wider latitude. The potencial development and conservation aspect described in this paper.